Infrared emission from the reaction of CHF ((X)over-tilde-(1)A') with NO - Brownsword, R; Hancock, G; Oum, K (1996)
Infrared emission has been observed from the reaction of the CHF (X̃1A′) radical with NO (X2Π). The carbene radical was formed by infrared multiphoton dissociation (IRMPD) of either the CH2FCl or the CH2F2 precursor, and emission in the 1850-4500-cm-1 region was observed by a time-resolved Fourier transform infrared (FTIR) technique. Emissions have been identified from the HF product of the reaction and from species produced by the subsequent reaction of the NCO radical product with NO. The HF was found to possess more than a statistical share of the available energy in vibration. Addition of D2 to the system results in DF formed from the reaction of F atoms, and comparison of the HF/DF emission intensities has allowed the relative branching ratio of the CHF + NO reaction forming HF and F products to be 0.6 ± 0.04:0.4 ± 0.03. © 1996 American Chemical Society.